Features of Using Thesaurus in Modern Information Search Systems - Prenov Barlikbay Barakbaevich,; Nurmaxanov Kayrat Erpayizovich,; D.Djumabaev,; Allaberganov Baxram Ismailovich, (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article describes the different approaches to the formalization of the thesaurus, information retrieval thesauri are described particularly with thesauri in information systems, as well as problems arise, to implement the requirements of the thesaurus. The peculiarities and differences of classifiers resources and conventional terminology and linguistic thesauri. We also consider the organization of user interfaces for use with a thesaurus and use them when searching for the information system, as well as thesauri administration interfaces.